INCREASING THE INTEREST OF PRIMARY SCHOOL STUDENTS IN MUSIC - Khalilova Makhfuza Makhamadjonovna; Shukurova Nigina Nasrullayevna (Bright Mind Publishing, 2025)
The article describes the interest of primary school students in music. Mainly in preschool education and the first grades of school, namely in primary school, music lessons and classes are conducted in a playful way, which is a very interesting activity and lesson for children. The article describes the methods and procedures for involving primary school students in music lessons.
Keywords: Listening to music, musical literacy, playing musical instruments, brass band, musician, singer, musical and didactic game.